Oron om cementens framtid, som kan ge hela Sverige kalla kårar! : -Har kalkbrytning på Slite någon framtid? - Landqvist, Patrik (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2022)
Sweden has historically been self-sufficient when it comes to produce and manufacturing concrete. Nowadays Sweden’s epicenter for lime extraction is located on the eastern island of Gotland, and the extraction base called Slite. Slite which is owned by Cementa account today for roughly 60-75% of the country lime extraction and is a major competitor on the European market. When it comes to producing limestone and thereafter fabrication of cement paste which is one of the main ingredients in concrete. Slite limestone has many advantages beyond share mass of lime. The Lime from Gotland is considered one of better one in the field and has the right composition to be used in various construction types of use. Concrete has different mixtures depending on the intended use and climate. Other then the limestone itself Gotland has many strategic advantages when in comes to the logistic aspect of reaching many markets. The lime extraction site is located near to the port of Slite which making hauling large quantity of limestone straightforward, and with shipping by freight reach large market in Northern Europe and North America.In the last couple of years has the future of Slite been in question. This summer an environment court outside of Stockholm reach a conclusion that Slites agreement would be rejected after the current one expires last October. The decision has sent shockwaves through the Swedish business establishment amongst them unions and large corporations who makes up large part of the Swedish economy.Impact assessment made by civil society business core and government alike shows the effect could be horrendous for many sectors with thousands of layoffs and recessions for many years to come. Many experts and scientist forecast chain consequences for many industries, for example the mine industry in northern Sweden which is heavily depended on concrete to secure their mining activities. A loss of production would cause a standstill for the likes of LKAB and SSAB the two main mine companies, which itself would ...